Analisis Kerja Sama Merida Initiative Antara Meksiko dan Amerika Serikat Dalam Mengurangi Drug Trafficking Organizations di Meksiko - Almira Farah Jelita; Khairur Rizki; Sirwan Yazid Bustami (The Department of International Relations Universitas Mataram, 2020)
Drug trafficking is one of main issue in Mexico. With its strategic geographical location, weak law enforcement in Mexico and the high demand for drugs from the United States have allowed the Mexican drug cartel to maintain its existence to date. With a border of 3,141 kilometers between the United States and Mexico consisting of deserts and barren mountains makes it difficult for the two countries to conduct surveillance in the border area. This is used by Mexican cartels to smuggle drugs into the United States. Drug trafficking carried out by the Mexican cartel not only has a negative impact on health, but also causes led to increased crime such as theft, violence, kidnapping and even murder in both countries. Mexican cartel activities pose a threat to the safety and health of citizens of the United States and Mexico. The two countries entered into a bilateral cooperation in the Merida Initiative in 2007 to tackle the narcotics problem. The purpose of this research is to see how the efforts made by Mexico and the United States in the Merida Initiative bilateral cooperation.